Complement activation by immunoglobulin does not depend solely on C1q binding. - Bindon, C; Hale, G; Waldmann, H (1990)
A matched set of rat chimeric antibodies has been studied for their ability to activate various key stages of the complement cascade. Rat IgM and IgG2b were efficient at all stages from C1q binding to cell lysis. However, for other isotypes, a direct correlation between C1q binding and cell lysis did not apply. IgG2a, which was only modestly efficient at C1q binding, was relatively more so for binding and activation of while C1, and was by far the most effective isotype after IgG2b and IgM for C4 and C3 binding. IgG2c was relatively efficient at binding C1q and C1, but less so for the binding of C4 or for later stages. IgA was efficient at binding C1, but again, this was not reflected in activation of later stages. The results suggest that properties of different isotypes, as well as influencing binding of C1q, may regulate attachment of the C1r2C1s2 tetramer. In addition, distinct features of certain isotypes may favor C4 activation and binding, independent of their ability to activate C1.